Generalized infantile myofibromatosis with visceral involvement presenting as diffuse hypopigmented macules at birth. Issue 1 (21st November 2020) - Saikaly, Sami K.; Schoch, Jennifer J.; Motaparthi, Kiran; Shenoy, Archana; Knapik, Jacquelyn A.; Bender, Nicole R.
Abstract: The initial clinical presentation of infantile myofibromatosis can vary from subtle skin changes to large tumors. Here, we describe a case of congenital generalized infantile myofibromatosis which presented with diffuse hypopigmented macules, some with subtle atrophy and telangiectasia. Further workup revealed visceral involvement which led to treatment with systemic chemotherapy. Awareness of this rare clinical presentation is crucial to expedite workup and treatment given the poor prognosis in infants with visceral involvement.